2015
DOI: 10.15829/1560-4071-2015-2-110-114
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Antagonists in Arterial Hypertension Treatment: Specifics of Lercanidipine

Abstract: 110Lercanidipine is a dihydropyridine calcium antagonist of the 3rd generation, with high level of vasoselectivity, long lasting effect and good antihypertensive effectiveness. the review shows the main specifics of pharmacokinetics and mechanism of action of the drug. It is known that lercanidipine supports renoprotection, left ventricle hypertrophy reduction, improvement of elastic properties of the vessels and central blood pressure decrease. sympathetic activation in lercanidipine is almost absent, that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
0
0
1
Order By: Relevance
“…Several studies have shown that CCB can protect the cell from damage of plasma membranes (ischemic, physical or chemical), leading to apoptotic cell death or necrosis in conditions of prolonged increasingof intracellular concentration of Ca 2+ . [10][11][12] This conclusion confirms the data obtained by us about the positive effect of CCB monotherapy on the electric charge of the RBC membrane (p<0.05). Also, in the absence of CCB in combined antihypertensive therapy, the lowest rates of AAEO were observed (combination of BB and ACE inhibitors; 42.3=6.3 mcm, p<0.05).…”
Section: Resultssupporting
confidence: 86%
“…Several studies have shown that CCB can protect the cell from damage of plasma membranes (ischemic, physical or chemical), leading to apoptotic cell death or necrosis in conditions of prolonged increasingof intracellular concentration of Ca 2+ . [10][11][12] This conclusion confirms the data obtained by us about the positive effect of CCB monotherapy on the electric charge of the RBC membrane (p<0.05). Also, in the absence of CCB in combined antihypertensive therapy, the lowest rates of AAEO were observed (combination of BB and ACE inhibitors; 42.3=6.3 mcm, p<0.05).…”
Section: Resultssupporting
confidence: 86%
“…За счет фиксации лерканидипина к липидному бислою мембраны глад-комышечных клеток сосудов возникает длительная блокада трансмембранных кальциевых каналов [23]. Ученые, проводившие эксперименты на крысах с ин-дуцированным сахарным диабетом, установили, что на-значение животным лекранидипина не только снизи-ло уровень артериального давления, но и затормози-ло развитие эндотелиальной дисфункции: произошла нормализация параметров эндотелий-зависимой ва-зодилатации, уменьшилась активность матриксных металлопротеиназ [24].…”
Section: Correction Of Endothelial Dysfunction In Hypertensionunclassified